Anticancer Potential of Fruit Extracts from Vatica diospyroides Symington Type SS and Their Effect on Program Cell Death of Cervical Cancer Cell Lines - Atchara Chothiphirat; Kesara Nittayaboon; Kanyanatt Kanokwiroon; Theera Srisawat; Raphatphorn Navakanitworakul (The Scientific World Journal)
Vatica diospyroides Symington is locally known as Chan-Ka-Pho in Thailand. Ancient people have used it as therapeutic plant for cardiac and blood tonic cure. The purpose of this study was to investigate the potential cytotoxicity and selectivity of the extracts from V. diospyroides type SS fruit on cervical cancer HeLa and SiHa cell lines and to examine its underlying mechanism of action. MTT assay revealed that the extracts showed inhibition of cell survival in a dose-dependent manner and exhibited highly cytotoxic activity against both HeLa and SiHa cells with IC50 value less than 20 μg/mL along with less toxicity against L929 cells. Acetone cotyledon extract (ACE) showed the best selectivity index value of 4.47 (HeLa) and 3.51 (SiHa). Distinctive morphological changes were observed in ACE-treated cervical cancer cells contributing to apoptosis action. Flow cytometry analysis with Annexin V-FITC and PI staining precisely indicated that ACE induced apoptosis in HeLa and SiHa cell lines in a dose-dependent manner. Treatment of ACE with half IC50 caused DNA fragmentation and also activated increasing of bax and cleaved caspase-8 protein in HeLa cells after 48 h exposure. The results suggest that ACE has potent and selective cytotoxic effect against cervical cancer cells and the potential to induce bax and caspase-8-dependent apoptosis. Hence, the ACE could be further exploited as a potential lead in cancer treatment.